Interleukin 2 and erythropoietin activate STAT5/MGF via distinct pathways. - Wakao, H (1995)
Signal transducers and activators of transcription (STAT) proteins play an important role in cytokine signal transduction in conjunction with Janus kinases (JAKs). MGF/STAT5 is known as prolactin regulated STAT. Here we demonstrate that interleukin 2 (IL-2) as well as erythropoietin (EPO) stimulate STAT5 and induce tyrosine phosphorylation of STAT5. These IL-2- and EPO-induced STATs have an identical DNA binding specificity and immunoreactivity. We also show that IL-4 induces a DNA binding factor which possesses similar, but distinct, DNA binding specificity from that of STAT5 and is immunologically different from STAT5. Analysis of two EPO receptor (EPOR) transfected CTLL-2 cell lines discloses that IL-2 activates JAK1 and JAK3 as well as STAT5, while EPO stimulates STAT5 and JAK2 in EPO-responsive CTLL-2 cells (ERT/E2). On the contrary, EPO activates neither JAK2 nor STAT5 in other cell lines that failed to respond to EPO (ERT cells). EPOR and JAK2 associate with each other regardless of EPO presence in ERT/E2 cells, however, such an interaction is not present in ERT cells. Thus, EPOR and JAK2 association seems to be important for EPO responsiveness in CTLL-2 cells.